Reduction of Rat Pleural Microvilli Caused by Noise Pollution - Maria João R. Oliveira (2003)
Scanning electron microscopy (SEM) was used to investigate whether chronic exposure to noise modifies pleural morphology. Rats were submitted to 8-h/day schedule of noise that is similar to the working hours at cotton-mill rooms. Morphometry of the area occupied by microvilli on the pleural surface showed a decrease in microvilli after 3 months of rat exposure to noise. The reduction of microvilli was 10% after 3 months of noise exposure (reaching 20% after 7 months of noise treatment) and is consistent with pleural effusions found in some of the patients working in noise-poluted environments.